(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to the current topic of modern science, the problems of the relationship between artificial intelligence and scientific and technological progress. In the modern information society, the role of artificial intelligence is progressing and is applied in all branches of science and technology. The article, based on factual materials, thoroughly shows the role and place of artificial intelligence in the modern development of science and technology.